2021
DOI: 10.1097/scs.0000000000007486
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Using Platelet Rich Fibrin (PRF) With Bone Graft in the Reconstruction of Alveolar Cleft, A Prospective Study

Abstract: Clefts of the lip, alveolus, and palate are the most common congenital malformation of the orofacial region. Bone grafting of the alveolar cleft is necessary for rehabilitation of oral function. Platelet rich fibrin (PRF), an autologous fibrin matrix is a secondgeneration platelet concentrate that has a positive effect on bone healing.Aim of the Study: The aim of this prospective study is to investigate and evaluate the quality and quantity of the bone graft that mixed with PRF when used in reconstruction of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…PRF-mixed particulate autogenous bone graft was used in the treatment of bone defects. Some studies demonstrated that PRF increase new bone formation and has a positive effect on early bone healing [20,29,30]. Based on PRP and PRF, Florian N. et al developed a new material termed mineralized plasmatic matrix (MPM), which contains platelets and fibrin concentrate in a liquid state; these materials can become bound to bone particles.…”
Section: The Grafting Tissue Of Choicementioning
confidence: 99%
“…PRF-mixed particulate autogenous bone graft was used in the treatment of bone defects. Some studies demonstrated that PRF increase new bone formation and has a positive effect on early bone healing [20,29,30]. Based on PRP and PRF, Florian N. et al developed a new material termed mineralized plasmatic matrix (MPM), which contains platelets and fibrin concentrate in a liquid state; these materials can become bound to bone particles.…”
Section: The Grafting Tissue Of Choicementioning
confidence: 99%
“…El plasma rico en fibrina (PRF) es una matriz de fibrina autóloga, un concentrado de plaquetas de segunda generación que ayuda mucho en la reparación ósea. 7 Según últimos estudios, el plasma rico en fibrina (PRF) con sus factores de crecimiento osteoinductivos y osteoconductivos mejoran en forma importante la reparación ósea de la FAP. 8 En la presente investigación, se muestra la experiencia a lo largo de 10 años en el manejo de la cirugía de injertos alveolares para la fisura alveolopalatina, a través de los procedimientos quirúrgicos.…”
Section: Wwwmedigraphicorgmxunclassified
“…Moreover, the use of bone grafts alone requires a long healing process, which may lead to some rate of relapse (bone resorption can reach up to 40%), compromising the clinical outcome and increasing the need for reintervention [1,4]. Thus, more recently, the concomitant use of natural-or synthetic-derived growth factors has been proposed to enhance the biological response, namely, by increasing the bone healing [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Rexhepi et al found that L-PRF or collagen membrane combined with inorganic bovine bone graft presented a similar effect on clinical attachment level in the treatment of infrabony defects, but L-PRF showed more radiographic defect bone level gain [18]. Al-Mahdi et al evaluated sixteen patients and reported that the L-PRF group (L-PRF mixed with an autogenous bone graft) increased bone density after 6 months and significantly reduced postoperative bone resorption compared with the control group [6]. Conversely, Omidkhoda et al showed no significant differences in the density and height of maxillary alveolar cleft reconstruction at three months with L-PRF [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation